The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/ppl.13563
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomics of PinusFusariumcircinatum interactions reveal metabolic clues to biotic stress resistance

Abstract: Fusarium circinatum, causing pine pitch canker (PPC), affects conifers productivity and health worldwide. Selection and breeding for resistance arises as the most promising approach to fight PPC. Therefore, it is crucial to explore the response of hosts with varying levels of susceptibility to PPC to unveil the genes/pathways behind these phenotypes. We evaluated the dynamics of the needle proteome of a susceptible (Pinus radiata) and a relatively resistant (Pinus pinea) species upon F. circinatum inoculation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 84 publications
1
10
0
Order By: Relevance
“…[ 72 ] The induction of the phenylpropanoids pathway has been previously reported in P. radiata after F. circinatum infection, [ 15,35,57 ] with recent proteomics studies suggesting that the host's secondary metabolism (e.g., lignans biosynthesis) may be targeted by the pathogen to negatively regulate pine immune response. [ 19 ] This is in accordance with the higher levels of phenolic compounds detected in inoculated P. radiata by RS. Raman data further indicates differences in the lignin subunits deposited in inoculated P. radiata plants, and thus structural differences in the lignin between inoculated and non‐inoculated samples.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…[ 72 ] The induction of the phenylpropanoids pathway has been previously reported in P. radiata after F. circinatum infection, [ 15,35,57 ] with recent proteomics studies suggesting that the host's secondary metabolism (e.g., lignans biosynthesis) may be targeted by the pathogen to negatively regulate pine immune response. [ 19 ] This is in accordance with the higher levels of phenolic compounds detected in inoculated P. radiata by RS. Raman data further indicates differences in the lignin subunits deposited in inoculated P. radiata plants, and thus structural differences in the lignin between inoculated and non‐inoculated samples.…”
Section: Discussionsupporting
confidence: 85%
“…[14][15][16][17][18] These have recently been complemented with physiological, multi-omics, and rhizobiome studies comparing one of the most PPC susceptible pine species (Pinus radiata D. Don) with a relatively resistant one (Pinus pinea L.) aiming to explore the onset of disease and identify specific mechanisms that may explain the differential responses observed. [12,[19][20][21][22] However, advances on the development of early detection tools for PPC are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Biotic stress research has also used genetic variance and proteomics aiming in this case at identifying the proteins responsible for resistance/susceptibility to two main pathogens affecting pine species worldwide currently: the fungus Fusarium circinatum , responsible for the pine pitch canker ( Wingfield et al., 2008 ; Amaral et al., 2021 ; Amaral et al., 2022 ), and the pine wood nematode Bursaphelencus xylophilus , causing pine wilt ( Espada et al., 2022 ). Comparative proteome analysis of the differential response of pine species upon F. cicinatum inoculation revealed that susceptibility was associated with proteins involved in negative regulation of plant immunity, and increased energy production and amino acid synthesis pathways related to changes in plant secondary metabolism and chloroplast redox balance.…”
Section: Proteomics Survey (2012-2022): Where Are We Now?mentioning
confidence: 99%
“…Comparative proteome analysis of the differential response of pine species upon F. cicinatum inoculation revealed that susceptibility was associated with proteins involved in negative regulation of plant immunity, and increased energy production and amino acid synthesis pathways related to changes in plant secondary metabolism and chloroplast redox balance. In turn, proteins related to vesicle trafficking and the crosstalk between ABA and epigenetic regulation were associated with pathogen resistance ( Amaral et al., 2021 ). Similar approaches have been used to study the interaction between pine species and the pine wood nematode, B. xylophilus .…”
Section: Proteomics Survey (2012-2022): Where Are We Now?mentioning
confidence: 99%
“…Induced defences require pathogen/pest recognition either through microbe‐/damage‐associated molecular patterns (MAMPs/DAMPs), resulting in pattern triggered immunity (PTI), or effector recognition by host resistance (R) proteins, resulting in effector triggered immunity (ETI; Agrios, 2005; Dodds & Rathjen, 2010; Jones & Dangl, 2006; Spoel & Dong, 2012). The majority of plant R proteins consist of nucleotide‐binding leucine rich repeat (NLR) receptors (Baggs et al, 2017; Głowacki et al, 2011).…”
Section: Introductionmentioning
confidence: 99%